The Effect Of Product Completeness, Price, And Promotion On Consumer Purchase Decisions At Sirandorung Fresh Fruit Shop Rantauprapat - Widiani, Endang; Pitriyani, Pitriyani; Siregar, Usmala Dewi (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
The rapid growth of the fruit retail industry requires researchers to understand the factors that can influence consumer purchasing decisions. Fruit sellers need to offer not only exceptional products, but also a wide selection, competitive prices, and effective marketing campaigns to stay relevant amidst changing consumer preferences. This study explores how product variations, prices, and promotional activities can influence consumer purchasing decisions at a Fresh Fruit Shop located in Sirandorung, Rantauprapat. A quantitative approach was taken through a survey, data collected by distributing questionnaires to customers of the Fresh Fruit Shop in Sirandorung. The analytical method applied is a multiple linear regression analysis, which evaluates the influence of each independent variable on the dependent variable. This research can provide insight into the key factors that influence consumers' final purchasing decisions. Practically, this research aims to provide business leaders with more efficient marketing strategies, while from an academic perspective, this research can contribute as a reference for future studies on consumer behavior in the fresh fruit retail sector.